Post-Totalitarian Nature and Regime Transition in the Republic of Armenia - Darbaidze, Eka; Niparishvili, Tamila (Politics / პოლიტიკა; 2023: მესამე ნომერი, 2023)
One of the central subjects of comparative studies is the study of democratization in Post-Soviet states. The practice of democratic modernization of post-totalitarian states clearly showed that they did not have many important social, political, economic, cultural and spiritual prerequisites for liberal-democratic transformations, which were characteristic of Western countries. The aim of the paper is to analyze the problems of democratization in post-Soviet Armenia and to discuss the Velvet Revolution of Armenia within the framework of these problems. On the road to democratic transition in Armenia, there were many problems, such as: the unresolved conflict in Nagorno-Karabakh, the oligarchic system of government, unfair elections, the government's pressure on the media and civil society, and, of course, the non-free judicial system. The revolution of 2018 brought new hopes and perspectives after the coming to power of Nikol Pashinyan, however, the developments in Nagorno-Karabakh, the defeat experienced in the second Karabakh war and the victory of Azerbaijan, after which Aliyev declared the sovereignty of Azerbaijan to be restored, presented a severe test to the young Armenian democracy and made the contours of democratization even more blurred. in country. The loss of Nagorno-Karabakh, which the Armenian people consider part of their identity, has presented the country with many problems. Today, it is difficult to predict to what extent Armenia under the leadership of Nikol Pashinyan will be able to overcome internal and external challenges and contribute to the formation of Armenia as a democratic state.
Keywords: Armenia, Post-Soviet Armenia, Democratization, Velvet revolution, Problems of democratization.